2002
DOI: 10.1063/1.1485111
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction studies of the magnetic phase transitions in Ce2Fe17 compound under pressure

Abstract: The influence of hydrostatic pressure (up to 5 kbar) on the magnetic structure of Ce2Fe17 was investigated using neutron diffraction in the temperature range from 2 to 300 K. The existence of a collinear ferromagnetic phase below 95 K with a magnetic moment of Fe, mFe=2.0 μB, was confirmed at ambient pressure. Magnetic peaks present between 95 and 205 K correspond to an incommensurate antiferromagnetic structure with a wave vector changing its value from τ1=0.026 Å−1 at 100 K to τ1=0.034 Å−1 at 205 K. A helica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 15 publications
4
45
1
9
Order By: Relevance
“…9 An extraordinary sensitivity of the ferromagnetic state of Ce 2 Fe 17 to the decrease of volume was confirmed by the magnetization and neutron diffraction measurements under pressure. 10,11 Both showed that a decrease of the volume leads to the suppression of the FM ground state and its substitution by the AFM one.…”
Section: Introductionmentioning
confidence: 99%
“…9 An extraordinary sensitivity of the ferromagnetic state of Ce 2 Fe 17 to the decrease of volume was confirmed by the magnetization and neutron diffraction measurements under pressure. 10,11 Both showed that a decrease of the volume leads to the suppression of the FM ground state and its substitution by the AFM one.…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi, à titre d'exemple, le diagramme de diffraction de la figure 3 présente l'évolution d'une partie du diagramme de diffraction neutronique de Ce 2 Fe 17 enregistré entre 2 et 300 K [17]. Ce composé présente une mise en ordre magnétique de type antiferromagnétique à T N = 205 K [17] cela se traduit, au refroidissement, par l'apparition sur le diffractogramme de pics de Bragg d'origine magnétique alors qu'à température ambiante les pics de Bragg ne sont dus qu'à l'ordre atomique.…”
Section: éTude De Transitions De Phases Magnétiquesunclassified
“…Ainsi, à titre d'exemple, le diagramme de diffraction de la figure 3 présente l'évolution d'une partie du diagramme de diffraction neutronique de Ce 2 Fe 17 enregistré entre 2 et 300 K [17]. Ce composé présente une mise en ordre magnétique de type antiferromagnétique à T N = 205 K [17] cela se traduit, au refroidissement, par l'apparition sur le diffractogramme de pics de Bragg d'origine magnétique alors qu'à température ambiante les pics de Bragg ne sont dus qu'à l'ordre atomique. Signalons que le caractère hélimagnétique de la structure antiferro adoptée par ce composé entre T N et T = 95 K conduit à des pics de Bragg magnétiques qui sont des satellites des pics nucléaires d'où leur notation sur la figure 3 (000) + , (101) − , (101) + (102) − [17].…”
Section: éTude De Transitions De Phases Magnétiquesunclassified
See 2 more Smart Citations